Esterification Reaction of Glycerol to The Derivatives Catalyzed by Amberlyst 36 - Aisyah, Aisyah; Rezeki, Rezeki; Firnanelty, Firnanelty; Abubakar, A. Nur Fitriani; Zahra, Ummi; Patunrengi, Iswadi Ibrahim; Nur, Arfiani (Hasanuddin University, 2021)
Several studies reported the use of acid catalysts of esterification of glycerol to acetin derivatives and amberlysts are no exception. However, among these strong sulfuric acid catalysts, amberlyst 36 is still rarely used and hence challenging to investigate. This study aimed to determine the yield and the selectivity of the esterification reaction of glycerol into acetine derivatives using a 5% of solid catalyst amberlyst 36 at a temperature of 90°C in a reflux system. The conversion value resulting from the reaction was 80.74%, with a selectivity value of 6.8% for triacetin. FTIR and GC-MS data support the monoacetin and triacetin structures. The findings indicate that the simple method and easily obtained catalyst can produce a high yield of acetin derivatives. This method is still possibly optimized to perform maximum yield with high selectivity.